MBL1 genotypes in wild boar populations from Sweden, Austria, the Czech Republic, and Japan - Bergman, I-M; Sandholm, K; Ekdahl, K N; Okumura, N; Uenishi, H; Guldbrandtsen, B; Essler, S E; Knoll, A; Heegaard, P M H; Edfors, I; Juul-Madsen, H R (International journal of immunogenetics, 2013)
The single nucleotide polymorphism (SNP) G949T in the mannose-binding lectin ( MBL ) 1 gene has been associated with low MBL-A concentration in serum and detected at different frequencies in various European pig populations. However, the origin of this SNP is not known. Part of the MBL1 gene was sequenced in 12 wild boar/Large White crossbred pigs from the second backcross (BC 2 ) generation in a family material originating from two wild boar x Large White intercrosses. Also, MBL-A serum concentration was measured in the entire BC 2 generation (n = 45). Furthermore, the genotypes of 68 wild boars from Sweden, Austria, the Czech Republic, and Japan were determined in regard to five previously described SNPs in MBL1 . The T allele of G949T was present among the BC 2 animals. MBL-A serum concentration in the BC 2 animals showed a bimodal distribution, with one-third of the animals at levels between 0.7 and 1.6 μg mL(-1) and the remaining pigs at levels around 13 μg mL(-1) . There was a co-variation between the presence of the T allele and low MBL-A concentration in serum. The genotyping of the wild boars revealed differences between populations. The T allele of G949T was not detected in the Austrian and Japanese samples and is thus unlikely to be an original feature of wild boars. In contrast, it was present at high frequency (0.35) among the Swedish wild boars, probably representing a founder effect. Five MBL1 haplotypes were resolved. Only two of these were present among the Japanese wild boars compared to four in each of the European populations. This difference may reflect differences in selection pressure and population history.
Keywords: Sus scrofa; Polymorphism, Single Nucleotide; sekvence nukleotidů; Czech Republic; zvířata; Rakousko; jednonukleotidový polymorfismus; Japonsko; Sweden; frekvence genu; Japan; Sequence Analysis, DNA; Mannose-Binding Lectin; Gene Frequency; Haplotypes; haplotypy; Receptors, Pattern Recognition; Genotype; genotyp; receptory rozpoznávající vzory; Austria; sekvenční analýza DNA; Animals; Base Sequence; Švédsko; Česká republika; lektin vázající mannosu